Towards a precision approach to anesthetic/analgesic immunomodulation in cancer - Gupta, Hersh V.; Tan, Kay S.; Fischer, Gregory W.; Mincer, Joshua S. (Frontiers in Anesthesiology, 2024)
Background: Immunomodulation is widely invoked to explain possible effects of anesthetic/analgesic drugs on recurrence and survival in cancer patients. By analogy with immune checkpoint inhibitors, which enhance anti-tumor actions of immune cells in the tumor microenvironment (TME), we aim to develop a precision approach to immunomodulation by anesthetic/analgesic drugs. We explore biomarkers predictive of immunotherapy response (tumor mutational burden (TMB)) and resistance (fraction genome altered (FGA)) in relation to anesthetic/analgesic dose to survival response and the expression of drug target receptor genes. Methods: Two local clinical cohorts (lung adenocarcinoma (LUAD) and colon adenocarcinoma (COAD) patients) were analyzed retrospectively to yield statistical interactions between drugs, outcomes, and TMB/FGA (extending previously reported results). Bulk tumor gene expression data for solid tumors from 6488 patients across 18 solid tumor types was obtained from The Cancer Genome Atlas (TCGA) and normalized by tumor type. TMB and FGA for each TCGA patient sample was extracted from cBioPortal. DeSeq was employed to quantify differential gene expression of target receptors of 79 common anesthetic/analgesic drugs for high/low TMB and FGA. Localization of these receptors to specific immune cells was estimated using CIBERSORT. Results: Increased TMB and FGA magnified opioid pro-tumor effects on overall survival in LUAD, while increased TMB reduced ketamine anti-tumor effects on recurrence and did not affect ketorolac anti-tumor effects on recurrence. In COAD, increased TMB (DNA mismatch repair deficiency) magnified opioid anti-tumor effects on recurrence. Drug target receptor gene expression (and immune cell-type specificity) correlated with both TMB and FGA as a function of cancer type. Conclusions: TMB and FGA may have utility as biomarkers predictive of individual cancer patient response to anesthetic/analgesic dose effects on survival due to immunomodulation. Correlation across cancer types of anesthetic/analgesic target receptor gene expression with TMB and FGA and with TME immune cell types suggests molecular/omics level targets for further mechanistic exploration. A precision oncoanalgesia approach in the cancer patient may ultimately be warranted to optimize oncological outcomes.